Dehumanization Toward Lucy Gray in The Hunger Games: The Ballad of Songbirds & Snakes (2023): An Analysis of Alienation - Novelita, Shabrina Sheila (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
Dehumanization is becoming a global issue nowadays and its reduction is spread through media technology, such as movies, to raise society’s awareness of the marginalized group. This research aims to identify the dehumanization mechanisms and how social inequality shapes the dehumanization of the main character in The Hunger Games: The Ballad of Songbirds & Snakes (2023). This alienation theory proposed by Karl Marx (1974) is used as an approach in analyzing the data. This research analyzes dialogue transcripts as the main data and scenes as well as audio as secondary data to reveal the issues. The results of the analysis indicate that the dehumanization mechanisms of Lucy Gray are legalized by the authoritarian government of the Capitol which also alienates the lower class into objects of entertainment shows, dangerous entities, and tools of winning. Moreover, two categories of social inequality, namely powerlessness and social classification, show how power and social status generate dehumanizing mechanisms.